La mort protestante : entre invisibilité et persistance. La difficulté d’ancrage des espaces funéraires protestants à Paris et à La Rochelle (XVIe-XVIIIe siècles) - Isabelle Souquet; Cécile Buquet-Marcon (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
From the 16th century, the Protestant Reformation spread rapidly but clandestinely through the kingdom of France, giving rise to eschatological opposition between Catholics and Protestants that crystallized around their places of burial. According to the political and geographic context, the Huguenots, who were still considered as heretics but tolerated under the Edict of Nantes, asserted their beliefs in silence and without ever disappearing, despite periods of exclusion and repression. Two French cities illustrate the complexity of responses to the coexistence of the two faiths: Paris, the royal and Catholic capital, and La Rochelle, a Protestant stronghold. In these two cities of opposing status, the management of cemeteries came under the majority religious authority. It would seem that despite opposing theologies, the burial practices of the two faiths ultimately followed the standards of Christian burials. The lack of textual data means that Protestant burials may only be identifiable by the topography of the chosen burial place, which was dictated by exclusion.